Reduplicazione in swahili. Iconismo e oltre (Atti del Sodalizio Glottologico Milanese, 2019)
The aim of this article is to deal with the semantics of reduplication in Swahili, on the basis of a list of 562 reduplicative words. In the first part of the work we will focus on the iconic values of reduplication, shared by most of the world languages; afterwards we will see how reduplication is applied beyond its iconic ground, spreading by semantic extension to some lexical fields. Notwithstanding what previous works on this subject claim, reduplication seems not to be used to express diminution. KEYWORDS: reduplication, Swahili, Bantu languages, iconism, semantics